Is there any potential or additive effect of anemia on hepatorenal syndrome? - Güngör, Gökhan; Akyıldız, Murat; Keskin, Muharrem; Solak, Yalçın; Gaipov, Abduzhappar; Bıyık, Murat; Çifçi, Sami; Ataseven, Hüseyin; Polat, Hakkı; Demir, Ali (Turkish Journal of Gastroenterology, 2016)
Abstract Background/Aims: Hepatorenal syndrome (HRS) is a severe complication of advanced cirrhosis and is characterized by renal dysfunction and poor survival rates. Although anemia is a non-rare condition in advanced liver cirrhosis, there is no publication regarding the potential or additive effects of anemia on HRS and renal dysfunction in patients with cirrhosis. We investigated whether severe anemia is a precipitant factor for HRS. Materials and Methods: In this prospective study, consecutive patients with cirrhosis with and without renal dysfunction were enrolled. A total of 29 patients with cirrhosis with HRS meeting the HRS diagnostic criteria (9 patients with type 1 HRS and 20 with type 2 HRS) and 37 patients with cirrhosis without HRS were included. The demographic features, laboratory data (particularly anemic parameters), and clinical scores of patients with and without HRS were evaluated. Results: Grades of ascites, Child–Turcotte–Pugh (CTP) scores, and Model of End Stage Liver Disease (MELD) scores were significantly higher in contrast to hemoglobin levels; hematocrit concentrations were significantly lower in patients with type 1 and 2 HRS than in those with non-HRS stable cirrhosis. There was a negative correlation between the hemoglobin–hematocrit and serum creatinine levels. In the logistic regression analysis, the hemoglobin levels and CTP and MELD scores were statistically significant for an onset of HRS. Conclusion: Anemia may contribute to HRS and deteriorated renal function in patients with HRS because anemic hypoxia can lead to microcirculatory renal ischemia in the kidneys and anemia can also activate sympathetic activity and hyperdynamic circulation in the pathogenesis of HRS.